Kurier Mazowsza . wiadomości Grup Oporu "Solidarni" RKW NSZZ "S[olidarność]" Mazowsze, no. 9, 1986 - ed. "Solidarni" Grupy RKW NSZZ "S" Reg. Mazowsze and TM [Tygodnik Mazowsze] (Grupy Oporu "Solidarni", 1986)
Creation and circulation: From issue no. 72(1989) published legally; In 1989 published in two formats 15 and 30 cm. The 30 cm edition with singlesided print was designed for noticeboards.